Peran Mediasi Job Distress pada Hubungan Politik Organisasional dan Perilaku Agresif: Analisis dengan Regresi Hirarkikal - Junaedi, Christofera Marliana; Darsono, Licen Indahwati (Fakutas Ekonomi Unika Widya Mandala Surabaya, 2006)
Though it is difficult to measure organizational politic is important to study, it is because organizational politics influence the behavior of organizations members. Respondents are lecturers and administrative employees. Results show that there is mediation role of job distress to organizational politics and aggressive behavior relation. This articles also discusses the relation of each variable.